EFEK HAMBATAN EKSTRAK DAUN CEPLUKAN (Physalis minima L)TERHADAP KONTRAKTILITAS OTOT POLOS USUS HALUS TERPISAH MARMUT DENGAN STIMULASI METAKOLIN EKSOGEN - Tarannita, Citra; Permatasari, Nur; Sudiarto, Sudiarto (Jurnal Kedokteran Brawijaya, 2006)
Physalis sp. has lots of merits as a kind of traditional medicine and one of them is its function as an alternatif treatment forÂ diarrhea. Physalis minima leaf contains alkoloid atropine which is assumed can inhibit the contractionof guinea pigâ€™sÂ isolated ileum smooth muscle. This research was to know the effect of Physalis minima leaf extract toward the contractionÂ of small intestine smooth muscle. This research was Â an experimental study using â€œThe Post Control GroupDesignâ€, andÂ guinea pigâ€™s isolated ileum as samples. The samples Â consisted of five guinea pigs, each sample was given four kinds ofÂ treatment. The control was given metacholine at the Â dose of 10Â -5Â without Physalis minima leaf extract. Before givingmetacholine at the dose of 10Â -5Â , the samples were given the first dosage of Physalis minima leaf extract (0.15%), theÂ second dose (0.30%) and the third dose (0.45%) so getting four graphs for each sample. The level of contraction wasÂ recorded by using kymograph. The result showed that Â the ileum contraction of the third group was inhibited (One WayÂ ANOVA, p=0.041), and there was a relation between the increasing dosage of Physalis minima leaf extract and theÂ decreasing ileum contraction (simple linear regression, with R=-0.608 p=0.04 and regression equation y=52.150 â€“Â 7.660x).